Finite element-based method for determining an optimal offloading design for treating and preventing heel ulcers. (April 2021) - Shaulian, Hadar; Gefen, Amit; Solomonow-Avnon, Deborah; Wolf, Alon
Abstract: Diabetic heel ulceration, a serious, destructive, and costly complication of diabetes, is often treated by custom-made offloading footwear. One common offloading device is a custom-made insole designed with a hole under the damaged site that is intended to reduce local mechanical loads on the ulcer. However, current devices do not take into account the increasing loads at the wound peripheries, and quantitative assessments and scientific guidelines for the optimal design of the offloading hole are lacking. Here, we develop a novel method to determine the volumetric exposure to mechanical loading of a human heel, at two volume of interests (VOIs) during walking in 150 different finite-element footwear configurations. We defined the two VOIs as (1) the area of the heel soft tissues typically at high risk of ulceration, and (2) the soft tissues surrounding the high risk area. For all model variants, three hole-geometry parameters were defined: (1) radius, (2) radius of curvature (ROC) and (3) depth. We found two combinations of the offloading parameters which minimize heel loads in both VOIs. The first is with a large offloading radius, large ROC and large depth, whereas the second is with a large offloading radius, large depth but relatively small ROC. Our novel practical scientific analysis method, that takes into account the ulcer site as well as the peripheral area, has the potential to optimize development of offloading solutions by streamlining the examination of their biomechanical efficiency, and thus may revolutionize prevention and treatment of diabetic ulcers at any foot location. Highlights: A novel analysis method to optimize offloading footwear design was exhibited. Our method has potential in prevention and treatment of diabetic foot ulcers. We accounted for maximum offloading of both the ulcer site and peripheral tissue. One optimal offloading design results from geometry close to the shape of the foot. Another optimal design includes large offloading hole and depth, and sharp edges.